2021
DOI: 10.1590/0103-8478cr20200310
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical fruit characterization, nutritional aspects and sensory analysis of dovyalis jams

Abstract: The objective of this study is to evaluate the composition, nutritional aspects and sensory analysis of the dovyalis jam. Dovyalis fruits were harvested from 4-year-old plants in the orchard of the Unioeste Experimental Farm. They were collected in the morning in polyethylene boxes, when they were ripe and with a purple coloration from the epicarp, being immediately transported to the Laboratory to prepare the jams. After fruits arrival, they were selected by size, color and weight and then sanitized in runnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…The rating for aroma showed that panelists placed preference to the sample with the least amount of salt and eggshell powder. Ratings for taste showed a slight difference among the samples 37 . Samples with less amount of salt and powder were preferred by the panelists.…”
Section: Sensory Evaluation Of Calcium-forti Ed Jelliesmentioning
confidence: 86%
“…The rating for aroma showed that panelists placed preference to the sample with the least amount of salt and eggshell powder. Ratings for taste showed a slight difference among the samples 37 . Samples with less amount of salt and powder were preferred by the panelists.…”
Section: Sensory Evaluation Of Calcium-forti Ed Jelliesmentioning
confidence: 86%
“…The bioavailability of anthocyanin and phenolic compounds present in fruits can be affected mainly by their use, cultivars, hybrids and climate conditions. Bromatological compounds are generally found in small fruits (Rotili et al, 2021;Rigolon et al, 2020;. Some studies were carried out with blackberry, regarding the qualification of these compounds (Teixeira et al, 2019), however, this influence on ripening and postharvest conservation is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the interest in fruits with sensory and bioactive properties that can promote health has increased. Thus, some specific native and exotic fruits have been explored because of their potential for fresh consumption and agroindustry (Rotili et al, 2018;Rotili et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among the exotic fruit crops from the Brazilian flora, D. hebecarpa is a lesser-known species that has great nutritional potential, health benefits, and high-value products. However, in Brazil, little is known about the fruit and it is underutilized Rotili et al, 2018;Rotili et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation